Faktor risiko kejadian gizi buruk di Kabupaten Lombok Timur, Provinsi Nusa Tenggara Barat - Khaerul Anwar; Muhammad Jufrrie; Madarina Julia (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2006)
Background: Despite numerous interventions, the preva- lence of severe malnutrition in under fives in the District of Lombok Timur during the last 5 years did not changed much and tended to increase.Objective: To assess risk factors for severe malnutrition, considered from points of view of family characteristics, children rearing practice and performance of posyandu, in 12 to 23 month-infants in the district.Methods: This was a case-control study. Cases were 65 severely malnourished children, while controls were a same number of children matched for age.Results: In bivariate analyses, variables identified as risk factors of severe malnutrition are low family income, OR(95%CI) of 5.0 (1.9-13.5), p=0.001; low maternal education, OR(95%CI) of 2.3 (1.1-4.9), p=0.02; low maternal knowledge on growth monitoring, OR(95%CI) of 15.6 (4.4-55.1), p<0.001; not cared by mother, OR(95%CI) of 7.8 (1.7-36.5), p=0.003; low birth weight, OR(95%CI) of 5.7 (1.2-27.3), p=0.02; short duration of exclusive breastfeeding, OR(95%CI) of 2.6 (1.3-5.2), p=0.008; incomplete immunization, OR(95%CI) of 10.3 (2.3-46.9), p<0.001; and the children’s feeding practice, OR(95%CI) of 3.3 (1.5-7.4), p=0.004. In multiple logistic regression, only maternal knowledge on growth monitoring was significantly associated with the risk of severe malnutrition.Conclusion: Family characteristic and children rearing practice were important risk factors of severe malnutrition in Lombok Timur District. Performance of posyandu is not associated with occurrence of severe malnutrition.